Nationalism in the English-speaking world - Hutchins-Viroux, Rachel; Tranmer, Jeremy (Cambridge Scholars, 2009)
A great deal has been written in recent years about nationalism. Yet scholars remain sharply divided as to a coherent theoretical model of this phenomenon and many have called for further empirical research. This volume pursues this line of inquiry, examining a variety of geographical contexts within the English-speaking world, including Australia, Canada, India, the United Kingdom and the United States at different historical periods. These interdisciplinary studies combine elements of socio ...